A Comprehensive Analysis of Break Bulk Port Efficiency Using an Analytic Network Process Model - Dinh, Gia Huy; Hoang, Phuong Nguyen; Nguyen, Lam Canh; Le Huu, Bao Tu; Dang Khoa, Pham Nguyen; Thuy Van, Nguyen Thi; Tai, Le Phuoc; Thuy Vi, Vu Thi; Xuan Huong, Nguyen (Society of Visual Informatics, 2025)
Ports significantly contribute to economic development, especially in developing nations. Although containerization prevails in cargo transportation, break bulk freight remains vital for items that cannot be accommodated in ordinary containers. This paper examines the successful techniques of breaking bulk terminals, concentrating on Vietnam, where these ports are essential to commerce. Employing qualitative and exploratory methodologies within the Entrepreneurial Action Theory (EAT) framework, data from 16 port executives at Vietnam's principal break bulk ports were examined to identify critical success factors, internal competencies, and external influences impacting port performance. The Analytic Network Process (ANP) ranks success factors, emphasizing cargo throughput and ship call stability as paramount, succeeding by profitability, operational efficiency, and customer happiness. External influences, such as the escalation of vessel sizes, port competition, and changes in international trade, profoundly influence port operations, necessitating adaptability and infrastructure investment. Government influence, developments in port technology, labor shortages, and cost changes are significant factors, whereas leadership vision and green initiatives, despite their lower ranking, possess long-term strategic importance. Moreover, internal success variables, including port infrastructure, labor proficiency, and technological integration, are crucial for sustaining efficiency. This study presents a conceptual framework for decision-makers in resource allocation and strategic planning by merging ANP findings with EAT. The findings enhance maritime research by providing insights for optimizing break-bulk operations and guaranteeing resilience in the face of growing industry challenges.